Assessment of the Environmental Footprint of Various Food Production Systems - Shalom, Donny (Journal of Food Sciences, 2024)
Purpose: This study sought to assess the environmental footprint of various food production systems. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the environmental footprint of various food production systems. Preliminary empirical review revealed that with a call for transformative changes to mitigate ecological impacts while ensuring food security and human well-being. Through a comprehensive analysis, significant variations in resource use and emissions were highlighted across different production methods. The study emphasized the interconnectedness between dietary choices, agricultural practices, and environmental outcomes, urging policymakers to enact evidence-based policies and agricultural stakeholders to adopt regenerative farming practices. Ultimately, the study served as a call to action for concerted efforts to transition towards a more sustainable and resilient food system, integrating ecological principles, social equity, and economic viability to promote harmony between human activities and the natural environment. Unique Contribution to Theory, Practice and Policy: The Systems theory, Ecological Economics and Agroecology models may be used to anchor future studies on the environmental footprint of various food production systems. The study made significant contributions to theory, practice, and policy in the realm of sustainable food production and environmental conservation. It advanced theoretical understanding by advocating for a systems-based approach to assessing environmental impacts and highlighting the importance of considering multiple dimensions of sustainability. In practice, the study recommended the adoption of agroecological approaches and the promotion of sustainable farming practices to mitigate environmental harm. Policy recommendations included the implementation of regulatory interventions and incentives to promote sustainability, while consumer education and international collaboration were emphasized for driving demand for sustainable food products and facilitating knowledge sharing. Lastly, the study underscored the importance of investment in research and innovation to drive continuous improvements in sustainable food production systems.